Natural Indole Alkaloids from Marine Fungi: Chemical Diversity and Biological Activities - Jiao Li; Chun-Lin Zhuang (Pharmaceutical Fronts, 2021)
Abstract The indole scaffold is one of the most important heterocyclic ring systems for pharmaceutical development, and serves as an active moiety in several clinical drugs. Fungi derived from marine origin are more liable to produce novel indole-containing natural products due to their extreme living environments. The indole alkaloids from marine fungi have drawn considerable attention for their unique chemical structures and significant biological activities. This review attempts to provide a summary of the structural diversity of marine fungal indole alkaloids including prenylated indoles, diketopiperazine indoles, bisindoles or trisindoles, quinazoline-containing indoles, indole-diterpenoids, and other indoles, as well as their known biological activities, mainly focusing on cytotoxic, kinase inhibitory, antiinflammatory, antimicrobial, anti-insecticidal, and brine shrimp lethal effects. A total of 306 indole alkaloids from marine fungi have been summarized, covering the references published from 1995 to early 2021, expecting to be beneficial for drug discovery in the future.